Towards an optimised lab procedure for long-term oxidative ageing of asphalt mix specimen. Issue Volume 17:Issued 6(2016) (2nd July 2016) - Steiner, Daniel; Hofko, Bernhard; Hospodka, Markus; Handle, Florian; Grothe, Hinrich; Füssl, Josef; Eberhardsteiner, Lukas; Blab, Ronald
Abstract : Ageing of bitumen leads to increased stiffness and brittleness. Thus, bituminous bound pavements become more prone to failure by low-temperature and fatigue cracking. Therefore, the ageing behaviour of bitumen has a crucial impact on durability, as well as recyclability of pavements. To assess ageing of bitumen, the rolling thin film oven test and pressure ageing vessel are standardised methods for short-term and long-term ageing in the lab. For lab-ageing of hot mix asphalt (HMA), various methods have been developed in the last decades. This paper presents a study on the potential of employing a highly oxidant gas for simulating the long-term oxidative ageing of asphalt mix specimens in the lab. Based on the results, an optimised lab-ageing procedure (Viennese Ageing Procedure – VAPro) for compacted HMA specimens to assess mix performance of long-term lab-aged specimens is developed. Thus, it is possible to optimise mix design not only for short-term performance but to take into account effects of oxidative ageing during its in-service life. VAPro is based on a triaxial cell with forced flow of a gaseous oxidant agent through the specimen. The oxidant agent is enriched in ozone and nitric oxides to increase the rate of oxidation. It is shown by stiffness tests of unaged and lab-aged specimens, as well as by Dynamic Shear Rheometer tests of recovered binder from aged specimens that asphalt mixes can be long-term aged at moderate temperatures (+60°C) and within 4 days and a flow rate of 1 l/min by applying VAPro. Thus, an ageing procedure is at hand that can simulate long-term ageing at conditions that are representative of conditions that occur in the field within an efficient amount of time.